Charge‐Induced Disorder Controls the Thermal Conductivity of Entropy‐Stabilized Oxides. Issue 51 (17th October 2018) - Braun, Jeffrey L.; Rost, Christina M.; Lim, Mina; Giri, Ashutosh; Olson, David H.; Kotsonis, George N.; Stan, Gheorghe; Brenner, Donald W.; Maria, Jon‐Paul; Hopkins, Patrick E.
Abstract: Manipulating a crystalline material's configurational entropy through the introduction of unique atomic species can produce novel materials with desirable mechanical and electrical properties. From a thermal transport perspective, large differences between elemental properties such as mass and interatomic force can reduce the rate at which phonons carry heat and thus reduce the thermal conductivity. Recent advances in materials synthesis are enabling the fabrication of entropy‐stabilized ceramics, opening the door for understanding the implications of extreme disorder on thermal transport. Measuring the structural, mechanical, and thermal properties of single‐crystal entropy‐stabilized oxides, it is shown that local ionic charge disorder can effectively reduce thermal conductivity without compromising mechanical stiffness. These materials demonstrate similar thermal conductivities to their amorphous counterparts, in agreement with the theoretical minimum limit, resulting in this class of material possessing the highest ratio of elastic modulus to thermal conductivity of any isotropic crystal. Abstract : The thermal, mechanical, and structural properties of a new class of high‐entropy ceramics, entropy‐stabilized oxides, are reported, to reveal that local ionic charge disorder can effectively reduce thermal conductivity without compromising mechanical stiffness. This work demonstrates the benefits of entropy stabilization to achieve unique combinations of thermophysical properties.